Gamification in Distance Learning in Corporate Training: A Literature Analysis - Patrycja MIZERA-PĘCZEK; Paweł ŁUCZAK (Communications of International Proceedings, 2023)
The article is devoted to the use of gamification mechanisms in distance learning training. The main aim is to answer two research questions: (QR1) What is the contemporary face of gamification? (QR2) What are the strengths and weaknesses of using gamification in training while people take part in online in the training? While answering the research questions, both a narrative and a systematic literature review were carried out. Its results indicate a great interest of researchers in both the psychophysical condition of students in distance learning conditions and the implementation of gamification mechanisms in achieving educational goals. The research results presented in the article confirm that gamification is a promising tool that increases students' motivation to learn and to interact with other students and the teacher. However, even though students are familiar with the virtualization of education and appreciate gamification in distance education, it is not able to fully compensate for direct contact with the teacher and other students.
Keywords: Gamification; Games; Training; Training Games; Distance Learning; Online Training; Pandemic